Определение Lr генов в сортах пшеницы мягкой озимой украинской селекции - Зайцева, Г.П.; Акинина, Г.Е.; Твердохлеб, Е.В.; Дугарь, Ю.Н.; Попов, В.Н. (Фактори експериментальної еволюції організмів, 2014)
Aims. The aim of our research was to identify Lr-genes in winter wheat Ukrainian varieties using DNA markers. Methods. DNA was isolated from a mixture of five seeds. Presence of Lr genes was studied by polymerase chain reaction (PCR). The amplification products were visualized by electrophoresis on a 2% agarose gel. For determination the numbers and sizes of the amplification products demo version of program TotalLab 120 was used. Results. Lr10 gene was detected in six varieties of winter wheat from two breeding centers – The Plant Production Institute (PPI) and The Plant Breeding and Genetics Institute (PBGI). In the studied varieties Lr19 and Lr20 genes were not identified. Lr34 gene was identified in 13 varieties of PPI, 17 varieties of PBGI and three varieties of the Mironivskiy institute of wheat (MIW). Conclusions. Using the DNA-markers varieties and lines of soft winter wheat with the Lr genes were identified. The two Lr genes, Lr10 and Lr34, are present in some studied samples. And two genes, Lr19 and Lr20, were not identified in studied Ukrainian winter wheat varieties and lines.

Key words: Lr- genes, DNA markers, leaf rust, T. aestivum L.